2010
DOI: 10.1099/mic.0.036251-0
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic flux analysis of wild-type Escherichia coli and mutants deficient in pyruvate-dissimilating enzymes during the fermentative metabolism of glucuronate

Abstract: The fermentative metabolism of D-glucuronic acid (glucuronate) in Escherichia coli was investigated with emphasis on the dissimilation of pyruvate via pyruvate formate-lyase (PFL) and pyruvate dehydrogenase (PDH). In silico and in vivo metabolic flux analysis (MFA) revealed that PFL and PDH share the dissimilation of pyruvate in wild-type MG1655. Surprisingly, it was found that PDH supports fermentative growth on glucuronate in the absence of PFL. The PDHdeficient strain (Pdh") exhibited a slower transition in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 48 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…coli strains have focused on metabolic engineering, aiming to understand how processes such as elevated intracellular pyruvate levels affect metabolite distribution 30, 31 or how central mutations trigger/alter metabolic fluxes 3234 . In recent years, technological advances have permitted detailed analyses of in vivo metabolism 35 , revealing its complexity and its influence on virulence and pathogenesis 36 .…”
Section: Discussionmentioning
confidence: 99%
“…coli strains have focused on metabolic engineering, aiming to understand how processes such as elevated intracellular pyruvate levels affect metabolite distribution 30, 31 or how central mutations trigger/alter metabolic fluxes 3234 . In recent years, technological advances have permitted detailed analyses of in vivo metabolism 35 , revealing its complexity and its influence on virulence and pathogenesis 36 .…”
Section: Discussionmentioning
confidence: 99%
“…1). In E. coli, the pflB deletion and its metabolic effects have been intensively investigated to enhance the yield of target products (35)(36)(37). Therefore, flask cultivation of pflB-deficient E. coli was compared with that of K. pneumoniae under microaerobic conditions for 24 h (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PDH, which converts pyruvate to acetyl-CoA with the generation of CO 2 and NADH, is typically active under respiratory conditions and the absence of activity under anaerobic conditions has been explained by its sensitivity to NADH inhibition (de Graef et al, 1999;Sawers and Clark, 2004). However, it has recently been shown that PDH plays a significant role in fermentative metabolism of glucose and glucuronate indicating that it can function under anaerobic conditions (Murarka et al, 2010a(Murarka et al, , 2010b. In addition, the highly reduced nature of the product distribution in the engineered E. coli strain (Table IV) may result in a lower NADH/NAD ratio, which could relieve some of the NADH inhibition on PDH.…”
Section: Kinetics Of Glycerol Consumption and Product Formation In Ementioning
confidence: 96%
“…The activity of methylglyoxal synthase was determined using a colorimetric assay (Berrios-Rivera et al, 2003). The activity of pyruvate dehydrogenase was measured as previously reported (Murarka et al, 2010a).…”
Section: Enzyme Activitiesmentioning
confidence: 99%